State and Prospects for Development of the Payment Card Market in Poland - Feruś Anna (Folia Oeconomica Stetinensia)
The development of innovative technologies has contributed to significant changes in the market for payment instruments. These changes have become a challenge for banks and have contributed to the continuous expansion of the products they offer, more technologically advanced, which will provide the customer with a high level of security. Banks, in order to meet customer expectations, are developing and improving the most popular distribution channels for their services, which are undoubtedly payment cards.